Flies use acetic acid to protect their offspring from parasitoids. - Kayla F Reddy; Aleksey Prok; Corinne M Stouthamer; Todd A Schlenke (PLoS Pathogens)
Plants and fungi often produce toxic metabolites, but herbivores and fungivores that evolve resistance to these toxins gain access to underutilized resources. An additional benefit of living in and consuming toxins is that animals can gain protection against non-resistant predators and parasites. The fruit fly Drosophila melanogaster consumes yeasts growing on rotting fruit and has evolved resistance to toxic fermentation products such as ethanol and acetic acid. We tested whether acetic acid protects flies from one of their most common natural enemies, parasitoid wasps, which infect fly larvae and pupae. We found that both wasp parasitism rate and wasp eclosion success are reduced when fly larvae are grown on acetic acid food, and wasp mothers actively avoid infecting fly larvae reared in acetic acid food if given a choice. In each case, acetic acid results in a greater fitness cost for a generalist parasitoid compared to a specialist parasitoid. Furthermore, fly mothers sense the presence of parasitoids in their environment and alter their oviposition behavior to lay eggs in more acetic acid-heavy food when wasps were present. This demonstrates that flies perceive the competing costs to their offspring of wasp parasitism and acetic acid toxicity but balance those costs to maximize offspring fitness.